A comparative analysis of root dentin transparency with known age - Singhal, Anita (Medknow Publications, 2010)
OBJECTIVE: To correlate dimensions of root transparency and age, and to assess whether transparency is reliable for age estimation of unknown. MATERIALS AND METHODS: 50 freshly extracted single rooted permanent teeth from 50 different individuals (27 males and 23 females) were collected and their ground sections of 400 μm were stained with 1% methylene blue. The area of the translucent zone was measured by superimposing a transparent graph paper on the ground section under stereomicroscope. The length of the translucency was measured by using digital vernier caliper. RESULTS: A strong positive correlation between age and translucency of dentin was noted. The length rather than the area of the translucent zone correlated more with age. CONCLUSION: Translucency of the root dentin increases with age and it can be used as a reliable parameter for the age estimation.